Understanding reform proposals presented by the World Bank and by the Pan-American Health Organisation : a guide for Caribbean Ministers of Health : a Study done for the CARICOM Secretariat - Theodore, Karl ([CCS] [Georgetown]GY, 1994)
Summarizes the main findings of the World Development Report 1993. Discusses the relevance of the report to the Caribbean and develops a framework for making the recommendations of the report more applicable to the countries of the region. Seeks to establish the link between the report and PAHO's Regional Plan for Investment in Health and the Environment in a way which provides a method to benefit from both.